2004
DOI: 10.1124/mol.104.000703
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Triazoloacridone C-1305 Is a Topoisomerase II Poison with Unusual Properties

Abstract: C-1305 [S-[[3-(dimethylamino)propyl]amino]-8-hydroxy-6H-vtriazolo[4,5,1-de]acridin-6-one] is a triazoloacridone with excellent activity in colon cancer models. The mechanism of C-1305 is unknown, although similarities in the chemical structure between C-1305 and amsacrine suggest common cellular targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…On the other hand, UGT1A10 expression slightly but significantly decreased the cellular response to C-1311, suggesting that the glucuronide metabolite of C-1311 may have lower activity than the parent compound. Thus, despite the subtle differences in structure and chemical properties between imidazoacridinones and triazoloacridinones (Lemke et al, 2004;Fedejko-Kap et al, 2012), the finding that the glucuronide of C-1305 is more toxic than the parent compound may be an important factor to be considered in evaluation of the clinical value and application of C-1305 versus C-1311. The differential cytotoxicities of the respective glucuronides are certainly intriguing given that the 8-OH group is in the structurally conserved portion of the molecules (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, UGT1A10 expression slightly but significantly decreased the cellular response to C-1311, suggesting that the glucuronide metabolite of C-1311 may have lower activity than the parent compound. Thus, despite the subtle differences in structure and chemical properties between imidazoacridinones and triazoloacridinones (Lemke et al, 2004;Fedejko-Kap et al, 2012), the finding that the glucuronide of C-1305 is more toxic than the parent compound may be an important factor to be considered in evaluation of the clinical value and application of C-1305 versus C-1311. The differential cytotoxicities of the respective glucuronides are certainly intriguing given that the 8-OH group is in the structurally conserved portion of the molecules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their clinical potential, the biologic and biochemical mechanisms of C-1305 and C-1311 action are still under extensive study (Mazerska et al, 2001(Mazerska et al, , 2003Augustin et al, 2006;Skwarska et al, 2007). Both compounds intercalate to DNA and inhibit topoisomerase II activity (Skladanowski et al, 1996;Dziegielewski et al, 2002;Lemke et al, 2004;Koba and Konopa, 2007). Furthermore, the lethal actions of these drugs appear to be due to covalent DNA cross-linking occurring only after metabolic activation (Dziegielewski and Konopa, 1996;Koba and Konopa, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of variance (two-way analysis of variance with Bonferroni post hoc analysis) was performed using GraphPad Prism (GraphPad Software Inc.). has been shown to influence specific interactions of C-1305 with DNA (Lemke et al, 2004). Therefore, one can suspect that changes in the electron density of the heterocyclic ring supported by the longer distance between the amino groups in the side chain as well as by the presence of more easily dealkylated methyl group are responsible for C-1305 being a better substrate for UGTs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that both compounds intercalate to DNA; however, physicochemical DNA binding is not crucial for the observed antitumor activity of these compounds (Dziegielewski et al, 2002;Koba and Konopa, 2007). It is postulated that the anticancer properties of these compounds are related to their inhibition of topoisomerase II activity (Skladanowski et al, 1996;Lemke et al, 2004) and interstrand covalent DNA cross-linking in tumor cells by metabolically activated compounds (Dziegielewski and Konopa, 1996;Koba and Konopa, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…C-1305 exhibits significant cytotoxic activity in vitro and potent antitumor activity towards a wide range of experimental tumors in mice (particularly leukemias, colon cancers and melanomas) [7] . This drug is a DNA topoisomerase II inhibitor that stabilizes covalent complexes between DNA and the topoisomerase enzyme [8] . Compared to classic topoisomerase II inhibitors, such as amsacrine, C-1305 produces only low levels of cleavable complexes.…”
Section: Introductionmentioning
confidence: 99%